Rede cegonha: seus principais indicadores e a situação atual do município de Mossoró/RN - Dias, Gabriel Nícolas de Melo (Universidade Federal Rural do Semi-Árido, 2020)
The Health Atention Networks are defined in your guidelines as organizational arrangements of health actions and services, from different technological densities, that get integrated through technical, logistical and management support systems, seek to guarantee comprehensive care. The ’Rede Cegonha’ aims to organize a model of care focused on prenatal care, childbirth and birth, the puerperium and the logistical system, all of which permeates maternal and child health. This strategy seeks to reduce maternal and child mortality rates, and related rates. This work sought to delimit the importance of these indexes in the management of ’Rede Cegonha’ and to analyze the current situation of its main indicators in the municipality of Mossoró / RN. The indicators of: infant mortality, maternal mortality, congenital syphilis, live births by maternal age, number of prenatal consultations, type of delivery and installed hospital capacity were evaluated. It was concluded that progress was made in most of these indicators, and that even greater incentive is needed in the maintenance and planning of the Rede Cegonha.
Keywords: Serviços de saúde materno-infantil; Atenção à saúde; Gestão em saúde; CIENCIAS DA SAUDE::MEDICINA